1999
DOI: 10.3758/bf03213121
|View full text |Cite
|
Sign up to set email alerts
|

Objects of attention, objects of perception

Abstract: Four experiments were conducted, to explore the notion of objects in perception. Taking as a starting point the effects of display content on rapid attention transfer and manipulating curvature, closure, and processing time, a link between objects of attention and objects of perception is proposed. In Experiment 1, a number of parallel, equally spaced, straight lines facilitated attention transfer along the lines, relative to transfer across the lines. In Experiment 2,with curved, closed-contour shapes, no "sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
127
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 16 publications
17
127
3
1
Order By: Relevance
“…The data that would most directly indicate a spread of attention are the probe response times for the peripheral locations within the rectangles in the different condition (i.e., rectangles without the target), and these response times were virtually identical whether the filler rectangles were present or not (411 vs. 412 msec). Because the probe technique has been repeatedly demonstrated as a sensitive measure of spatial attention (Cave & Zimmerman, 1997;Kim & Cave, 1995, 1999Kramer, Weber, & Watson, 1997), it is unlikely that our results were due to lack of sensitivity. Instead, the most probable explanation is that a narrow focus of spatial attention is maintained even when the filler trials are included.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The data that would most directly indicate a spread of attention are the probe response times for the peripheral locations within the rectangles in the different condition (i.e., rectangles without the target), and these response times were virtually identical whether the filler rectangles were present or not (411 vs. 412 msec). Because the probe technique has been repeatedly demonstrated as a sensitive measure of spatial attention (Cave & Zimmerman, 1997;Kim & Cave, 1995, 1999Kramer, Weber, & Watson, 1997), it is unlikely that our results were due to lack of sensitivity. Instead, the most probable explanation is that a narrow focus of spatial attention is maintained even when the filler trials are included.…”
Section: Resultsmentioning
confidence: 52%
“…Past research has shown that the manifestation of object effects is influenced by a number of factors, including the quality of the object representation and the participants' subjective organization of a stimulus pattern (Avrahami, 1999;Chen, 1998;Watson & Kramer, 1999). For example, response latencies to a target differ as a function of whether the stimulus pattern is perceived as being made of one object or two objects (Chen, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using dynamic displays with moving objects, a number of studies found object-based IOR (e.g., Chou & Yeh, 2008;Gibson & Egeth, 1994;Jordan & Tipper, 1998, 1999List & Robertson, 2007;Tipper, Driver, & Weaver, 1991;Tipper, Weaver, Jerreat, & Burak, 1994). Tipper et al (1991) cued attention to a moving object and found that IOR moved with the object to a new location, rather than remaining at the original environmental location.…”
Section: Outside Object (B) Inside Object (A)mentioning
confidence: 99%
“…In psychologic experiments, psychologists have found that shifting attention within an object should be easier than shifting attention between objects, which is also called same-object effect [7]. That is to say, when the object is attended, all the details in the object will be attended thereafter.…”
Section: Object-based Attention Modelmentioning
confidence: 99%